Modeling habitat distribution and niche overlap of Asian horseshoe crabs: Implications for conservation - Jian Liao; Chun-Hui Xiong; Gao-Cong Li; Jia-Yu Li; Yuan-Feng Yang; Shui-Yuan Zhang; Yi-Yang Li; Kai-Lin Zeng; Mei-Ling Hu; Yu-Song Guo; Zhong-Duo Wang (PLoS ONE, 2025)
Asian horseshoe crabs are ancient organisms essential for the balance of marine ecosystems. However, detailed information on their ecology and the environmental factors influencing their distribution remains limited. In this study, we analyzed habitat characteristics, potential distribution, and niche overlap for three species: Tachypleus tridentatus, Carcinoscorpius rotundicauda, and Tachypleus gigas. Predictive modeling using MaxEnt and niche analysis revealed that water depth and distance to land are key factors determining species distribution, with species-specific environmental influences: T. tridentatus is affected by maximum summer chlorophyll-a, C. rotundicauda by minimum chlorophyll-a, and T. gigas by wind speed. In terms of niche overlap, the highest degree of overlap was observed between C. rotundicauda and T. gigas, while the overlap between T. tridentatus and T. gigas was the lowest. The results highlight priority conservation areas, providing insights for management and protection strategies amid current environmental threats.